2011
DOI: 10.1007/s00204-011-0696-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of enzymatically modified isoquercitrin on phenobarbital-induced liver tumor promotion in rats

Abstract: To investigate the effect of enzymatically modified isoquercitrin (EMIQ) on hepatocellular tumor promotion induced by phenobarbital (PB), male rats were administered a single intraperitoneal injection of 200 mg/kg N-diethylnitrosamine (DEN) and then fed with a diet containing PB (500 ppm) for 8 weeks, with or without EMIQ (2,000 ppm) in the drinking water. One week after PB administration, rats underwent a two-thirds partial hepatectomy. The PB-induced increase in the number and area of glutathione S-transfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…These results suggest that ORPH mainly induces CYP2B during the metabolic process in the rat liver. It has been reported that chemicals that induce CYP2B and have a hepatic tumor promoting activity produce ROS during the metabolism of these, and the resulting oxidative stress stimulates the tumor promoting effect in the rat liver (Dewa et al, 2009;Morita et al, 2011). In the present study, ROS production was increased in rats given 750 ppm ORPH or more, and the level of TBARS and 8-OHdG was increased in the DEN-High ORPH group.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results suggest that ORPH mainly induces CYP2B during the metabolic process in the rat liver. It has been reported that chemicals that induce CYP2B and have a hepatic tumor promoting activity produce ROS during the metabolism of these, and the resulting oxidative stress stimulates the tumor promoting effect in the rat liver (Dewa et al, 2009;Morita et al, 2011). In the present study, ROS production was increased in rats given 750 ppm ORPH or more, and the level of TBARS and 8-OHdG was increased in the DEN-High ORPH group.…”
Section: Discussionsupporting
confidence: 52%
“…The nuclear translocation of CAR induced by PB stimulates the expression of various genes that enhance hepatic tumor promotion (Deguchi et al, 2009;Kawamoto et al, 1999). In addition, it has been shown that microsomal ROS production and production of thiobarbituric acid-reactive substances (TBARS) and are induced by PB with increasing the Cyp2b (Morita et al, 2011). Taking these facts into account, we hypothesize that ORPH has a liver tumor-promoting activity similar to the activity of PB.…”
mentioning
confidence: 87%
“…The phenobarbital increased oxidative stress with the formation of ROS and activation of CAR. The group treated with EMIQ showed a significant decrease in oxidative stress markers in addition to inhibition of MAPK and CAR pathways, confirming the antioxidant and antiproliferative actions of this molecule [88,89] . A study investigated the effects of enzymatically modified IQ on preneoplastic liver cell lesions induced by thioacetamide promotion in a hepatocarcinogenesis rat model.…”
Section: Liver Cancersupporting
confidence: 52%
“…Enzymatically modified IQ suppressed the liver tumorpromoting activity of phenobarbital by inhibiting nuclear translocation of constitutive active/androstane receptor (CAR), and not by suppressing oxidative stress in rats. Morita et al [88] investigated the action of EMIQ in an experimental model of liver tumor induced by phenobarbital, a sedative and antiepileptic drug. The phenobarbital increased oxidative stress with the formation of ROS and activation of CAR.…”
Section: Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation